Pro SharePoint 2013 app development - Wright, Steve (Apress Imprint: Apress, 2013)
Apps have taken the world by storm, and now they're taking SharePoint as well. The biggest new thing in SharePoint 2013, apps are the solution to creating custom code that runs on not just your own SharePoint deployment, but also on others' implementations as well. Pro SharePoint 2013 App Development is your must-have guide to developing app solutions that run on the SharePoint 2013 platform. Using step-by-step tutorials, author Steve Wright creates a sample SharePoint app throughout the course of the book, and you can walk with him through the entire lifecycle of a SharePoint app. Get expert guidance and advice on creating an app, provisioning it for use in SharePoint, securing it from unauthorized use and from other applications, integrating your app with SharePoint search and other platform features, and much more. You'll even discover how to present your app to users on mobile devices like iPads, smartphones, and Microsoft Surface tablets. Apps in SharePoint are here to stay. Don't miss out - pick up a copy of Pro SharePoint 2013 App Development and get started on your own custom apps today. Introduces the architecture for creating and hosting SharePoint apps. Leads the reader through the creation and deployment of a complete solution. Provides an understanding of the security features in the SharePoint app model. Helps the organization leverage internal data securely over the network. Leverages SharePoint search and other services to create rich SharePoint solutions. Introduces the techniques for delivering data on a multitude of web and mobile platforms.